A Conceptual Framework of Islamic Religious Education for Strengthening Religious Moderation in a Multicultural Society - Fatmawaty Padedeng; ST. Wardah Hanafie Dos (Prodi PAI STIT Sunan Giri Bima, 2026)
Religious moderation has become a strategic educational agenda in multicultural societies as a response to the increasing challenges of religious intolerance, radicalism, and socio-cultural polarization. Although numerous studies have examined the relationship between Islamic Religious Education (IRE) and religious moderation, existing research generally focuses on individual educational components, such as curriculum, teachers, learning strategies, or institutional policy, without explaining the systematic relationship among these components. This study aims to develop a Conceptual Framework of Islamic Religious Education for Strengthening Religious Moderation in a Multicultural Society. The study employed a Systematic Library Research (SLR) approach by analyzing peer-reviewed journal articles published between 2020 and 2025 and indexed in Scopus, Web of Science, DOAJ, and SINTA. The selected literature was synthesized using Thematic Analysis to identify recurring concepts and reconstruct theoretical relationships. The findings reveal five interconnected dimensions of the proposed framework, namely Input (Wasatiyyah values, multicultural society, and national commitment), Islamic Religious Education (curriculum, teacher competence, learning strategies, school culture, and digital literacy), Internalization Process (dialogue, reflection, habituation, experiential learning, and collaborative learning), Output (religious character, tolerance, justice, inclusiveness, and mutual respect), and Outcome (religious moderation, social harmony, and a peaceful multicultural society).